Convenient Preparation of Long-Chain Dialkyl Phosphates: Synthesis of Dialkyl Phosphates - Aitken, R. Alan; Collett, Chris J.; Mesher, Shaun T. E. (Synthesis, 2012)
Reaction of phosphorus oxychloride with a primary alcohol (1.8 equiv) and triethylamine (1.8 equiv) in toluene, followed by filtration and treatment with steam, gives dialkyl phosphates in good yield and essentially free from trialkyl phosphate contamination.
Keywords: dialkyl phosphates; esterification; hydrolysis; hydraulic fracturing; enhanced oil recovery